Penggunaan Sari Umbi Bawang Dayak (Eleutherine americana Merr) sebagai Pewarna Alternatif untuk Pemeriksaan Telur Cacing (Ascaris lumbricoides) - Enzelita Andini (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The long-term use of eosin can cause carcinogenic effects, meaning it has the potential to induce cancer, and its resulting waste may also pollute the environment. Therefore, there is a need for alternative dyes that are safer and more environmentally friendly. One possible option is natural dyes, such as extracts from the bulbs of Dayak onions (Eleutherine palmifolia). The Dayak onion bulb contains natural pigments from the flavonoid group, which can produce red, orange, blue, and purple hues, making it a potential substitute for synthetic eosin. This study aims to compare the staining quality between natural eosin and synthetic dyes. The method used was experimental, employing Dayak onion bulb extract at concentrations of 2%, 4%, and 6%. The samples tested were feces that were positive for Ascaris lumbricoides eggs. The results showed that staining using Dayak onion bulb extract did not yield optimal results and was considered less effective for examining Ascaris lumbricoides eggs. Thus, the Dayak onion bulb extract cannot yet be used as an alternative to eosin dye in such examinations.